Differential mouse-strain specific expression of Junctional Adhesion Molecule (JAM)-B in placental structures. Issue 1 (3rd March 2016) - Stelzer, Ina Annelies; Mori, Mayumi; DeMayo, Francesco; Lydon, John; Arck, Petra Clara; Solano, Maria Emilia
ABSTRACT: The junctional adhesion molecule (JAM)-B, a member of the immunoglobulin superfamily, is involved in stabilization of interendothelial cell-cell contacts, formation of vascular tubes, homeostasis of stem cell niches and promotion of leukocyte adhesion and transmigration. In the human placenta, JAM-B protein is abundant and mRNA transcripts are enriched in first-trimester extravillous trophoblast in comparison to the villous trophoblast. We here aimed to elucidate the yet unexplored spatio-temporal expression of JAM-B in the mouse placenta. We investigated and semi-quantified JAM-B protein expression by immunohistochemistry in early post-implantation si tes and in mid- to late gestation placentae of various murine mating combinations. Surprisingly, the endothelium of the placental labyrinth was devoid of JAM-B expression. JAM-B was mainly present in spongiotrophoblast cells of the junctional zone, as well as in the fetal vessels of the chorionic plate, the umbilical cord and in maternal myometrial smooth muscle. We observed a strain-specific placental increase of JAM-B protein expression from mid- to late gestation in Balb/c-mated C57BL/6 females, which was absent in DBA/2J-mated Balb/c females. Due to the essential role of progesterone during gestation, we further assessed a possible modulation of JAM-B in mid-gestational placentae deficient in the progesterone receptor ( Pgr −/− ) and observed an increased expression of JAM-B in Pgr −/− placentae, compared to Pgr +/+ tissue samples. We propose that JAM-B is an as yet underappreciated trophoblast lineage-specific protein, which is modulated via the progesterone receptor and shows unique strain-specific kinetics. Future work is needed to elucidate its possible contribution to placental processes necessary to ensuring its integrity, ultimately facilitating placental development and fetal growth.